2009
DOI: 10.1111/j.1753-4887.1984.tb02315.x
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate-2-Sulfate Metabolism in Fish

Abstract: a potentially fatal condition resulting S from inadequate hydroxylase activity, and causing reduced collagen formation, has been known and feared since ancient times. Its prevention and cure were associated with consumption of fresh fruitsespecially citrusbut it was not until 1928 that the antiscorbutic factor was identified. Although most vertebrate animals synthesize L-ascorbic acid (AA), several species (primates, guinea pigs, fish, bats, insects and some birds) lack the ability to produce L-gulonolactone o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 39 publications
0
4
0
2
Order By: Relevance
“…The variation of the requirement AsA value for sea cucumber may be attributed to the fish species, sizes, form of AsA, experimental conditions and nutrient interrelationships in different studies (Halver ; NRC ). On the other hand, the utilization of different forms of dietary AsA is different in fish (Dabrowski, Matusiewicz & Blom ).The LAPP used in the present study has shown to have AsA activity for fish (Tucker & Halver ; Grant, Seib, Liao & Corpron ; Wilson, Poe & Robinson ), which accounted for requirement differences. Furthermore, the effect on growth performance for sea cucumber fed diet containing 0–598 mg AsA kg −1 (in the form of LAPP) is scarce, requires further research.…”
Section: Discussionmentioning
confidence: 78%
“…The variation of the requirement AsA value for sea cucumber may be attributed to the fish species, sizes, form of AsA, experimental conditions and nutrient interrelationships in different studies (Halver ; NRC ). On the other hand, the utilization of different forms of dietary AsA is different in fish (Dabrowski, Matusiewicz & Blom ).The LAPP used in the present study has shown to have AsA activity for fish (Tucker & Halver ; Grant, Seib, Liao & Corpron ; Wilson, Poe & Robinson ), which accounted for requirement differences. Furthermore, the effect on growth performance for sea cucumber fed diet containing 0–598 mg AsA kg −1 (in the form of LAPP) is scarce, requires further research.…”
Section: Discussionmentioning
confidence: 78%
“…All of these factors could cause the wastage of AsA (Hilton, Cho & Slinger ; Lovell & Lim ; Soliman, Jauncey & Roberts ; Shiau & Hsu ; Conklin, Akiyama & D'Abramo ). The more stable forms of AsA such as l ‐ascorbyl‐2‐sulphate, LAPP, AMP‐Na/Ca and AMP‐Mg which exhibited high resistance to oxidation have been used to investigate vitamin C requirement of fish and penaeid shrimp (Tucker & Halver ; Shigueno & Itoh ; Wilson, Poe & Robinson ; He & Lawrence ; Chen & Chang ; Hsu & Shiau , ; Moreau, Cuzon & Gabaudan ; Cavalli, Batista, Lavens, Sorgeloos, Nelis & De Leenheer ). LAPP used worldwide as a source of vitamin C is extremely stable under harsh feed manufacturing and storage conditions (Grant, Seib, Liao & Corpton ; Gadient & Schai ; Keefe ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Ascorbic acid was reported to inhibit the binding of AFB1 to DNA (Yu et al, 1994). In addition, AA is required for the hydroxylation of essential amino acids and of several oxidase enzymes (Tucker and Halver, 1984;Dawson et al, 1990).…”
Section: Mortality Ratementioning
confidence: 99%